Variations in plant–microbe–soil C:N:P stoichiometry along a 900-year age gradient in Torreya grandis ‘Merrillii’ plantations in Southeast China - He, Sijia; Huang, Juying; Na, Xiaofan; Huang, Shengyi; Fang, Zhao; Zhang, Shuoxin; Zhou, Zhichun; Wang, Bin (Frontiers in Sustainable Food Systems, 2024)
Researches on the ecological stoichiometry of forest vegetation at different growth stages under long-term human management activities and its driving factors will help to clarify how the limited nutrient resources are allocated at different growth stages of forests, providing a basis and suggestions for scientific cultivation of artificial forests.In subtropical China, the C:N:P stoichiometry of an ancient Torreya grandis 'Merrillii' community was measured in leaves, twigs, roots, soils, and soil microbes with age gradients of 0-50, 50-100, 100-300, 300-500, and more than 500 years. The results showed that the nutrient use varied with tree ages. The N and P concentrations in the leaves, twigs, and roots of T. grandis had the similar increasing trends with the increasing tree age, and the N concentrations in leaves in 0-50-year-old forests were significantly lower than those forests of other ages. Particularly, the N:P ratio of different organs was always below 10, reflecting limited N supply of plants. The soil C content increased with the increasing T. grandis forest ages while the soil microbe C showed a fluctuated trend. There was a higher correlation among the C, N and P contents and their ratios in leaves, twigs and roots of 0-50-year-old forests than that in soil microbes, but inversely at more than 500-year-old forests. The homeostasis analysis results showed that the roots and soil microbes are more indicative of soil nutrient availability. The results of redundancy analysis showed that acid phosphatase activity had the highest impact on soil microbes in 0-10 and 10-20 cm soil layers, confirming that the decomposition and transformation of P in soils is very active. Moreover, soil enzyme activity mediates the influence of soil microbes on soil N and P limitation. In summary, tree age can effect the plant-microbe-soil C:N:P stoichiometry of T. grandis forests. The growth of T. grandis is mainly restricted by N, and reasonable application of N fertilizer is needed to promote its growth.